2020
DOI: 10.1130/g47304.1
|View full text |Cite
|
Sign up to set email alerts
|

Mesozoic juvenile crustal formation in the easternmost Tethys: Zircon Hf isotopic evidence from Sumatran granitoids, Indonesia

Abstract: Prior to the collision of India with Asia, the evolution of island arcs and resultant crustal formation in the now-disrupted easternmost Tethys are poorly constrained. Here, we report for the first time zircon U-Pb and Hf isotopic data from Mesozoic granitoids in Sumatra, Indonesia. Our analyses identified three magmatic episodes at 214–201 Ma, 148–143 Ma, and 102–84 Ma, respectively, with a drastic change in magmatic zircon εHf(t) values from –13.1 to +17.7 in the Late Triassic granitoids, which reveals a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…After the Middle Jurassic (170-∼70 Ma), West Borneo was possibly affected by back-arc extension and experienced increased magmatism associated with a seaward younging trend in the overriding plate (Figure S1 in Supporting Information S1), caused by slab steepening or rollback (Figure 5f). The simplest explanation of our results in terms of periods of compression, breaks, and flare-ups of magmatism and changes in the younging direction of magmatism is that west dipping subduction of the Paleo-Pacific slab underwent periodic shallowing and steepening of slab dip, similar to that observed in other long-lived volcanic arcs including the Central Andes and Neo-Tethyan arc system from southern Tibet to Sumatra (Li et al, 2020;Zhang et al, 2019).…”
Section: Implication For Paleo-pacific Slab Dip Anglessupporting
confidence: 65%
“…After the Middle Jurassic (170-∼70 Ma), West Borneo was possibly affected by back-arc extension and experienced increased magmatism associated with a seaward younging trend in the overriding plate (Figure S1 in Supporting Information S1), caused by slab steepening or rollback (Figure 5f). The simplest explanation of our results in terms of periods of compression, breaks, and flare-ups of magmatism and changes in the younging direction of magmatism is that west dipping subduction of the Paleo-Pacific slab underwent periodic shallowing and steepening of slab dip, similar to that observed in other long-lived volcanic arcs including the Central Andes and Neo-Tethyan arc system from southern Tibet to Sumatra (Li et al, 2020;Zhang et al, 2019).…”
Section: Implication For Paleo-pacific Slab Dip Anglessupporting
confidence: 65%
“…1), in particular, have interacted with major tectonic events such as continental deformation and propagating extrusion owing to the collision of India into Eurasia (Tapponnier et al, 1982;Schellart et al, 2019). We report our finding of volcanic migration in the middle Miocene in northwestern Sumatra as part of the outcome of a systematic investigation on the magmatism of the island (Lai et al, 2019;Zhang et al, 2019;Li et al, 2020) (Fig. 1).…”
Section: Introductionmentioning
confidence: 53%
“…As synthesized by Barber et al (2005), K-Ar ages obtained mainly by Bellon et al 2004, along with sparse age and geochemical data reported by earlier studies, indicate that magmatism in Sumatra can be divided into several pre-Cenozoic stages and five subsequent stages active from the Paleocene to recent. Magmatic stages from pre-Cenozoic to recent may be affiliated with a change in the subduction system that started operating in the eastern portion of the Paleo-Tethys and persists to the modern Indo-Australian system in Southeast Asia (Hall, 2012;Metcalfe, 2013;Zhang et al, 2019;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Wharton Fossil Ridge and Investigator Fracture Zone on the Indian Ocean floor also subduct obliquely beneath northern Sumatra (Koulakov et al., 2016; Lange et al., 2010; S. Liu et al., 2018). Arc magmatism on Sumatra can be traced back to the Triassic by the Meso‐Tethys Ocean subduction and later to the Late Cretaceous (∼100 Ma) by the Neo‐Tethys Ocean subduction (Barber et al., 2005; S. Li et al., 2020), leading to Mesozoic and Cenozoic juvenile crustal formation on Sumatra Island (S. Li et al., 2020; Zhang et al., 2019). The volcanoes along the Sunda arc are located close to a ∼1,900 km long right‐lateral strike‐slip Sumatra Fault system that traverses the length of Sumatra between the Andaman and Java Seas (Figure 1a; Sieh & Natawidjaja, 2000).…”
Section: Geological Settings and Samplesmentioning
confidence: 99%